Rediscovery of the Simalur Island Flying Fox Pteropus hypomelanus simalurus (Chiroptera: Pteropodidae) after 113 Years - Muhammad Iqbal; Elfira Septiansyah; Silvi Dwi Anasari; Asman Adi Purwanto; Nurina Indriyani; Irda Kusuma; Tom Amey (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2026)
The Simalur Island Flying Fox Pteropus hypomelanus simalurus is a poorly known insular taxon historically recorded from Simeulue Island in the early twentieth century. However, since the original record, no confirmed scientific observations had been reported for more than a century, leading to considerable uncertainty regarding its persistence and conservation status. In April 2026, field surveys across Simeulue Island and several surrounding satellite islands documented two colonies of Pteropus sp. within the archipelago. More than 500 individuals were recorded on 9 April 2026 on Linggam Island, while approximately 100 individuals were observed on 17 April 2026 in Labuhan Bakti, Simeulue Island. The observed flying foxes are provisionally assigned to P. h. simalurus based on external morphology and geographic distribution. Individuals closely matched the original description of the taxon, exhibiting a predominantly black head, dark underparts, black back and rump, and a dull golden to chestnut mantle. Although morphometric and molecular confirmation is still required, the observed individuals correspond closely with the historical description and known range of P. h. simalurus. These records represent the first confirmed scientific observations of this taxon in more than a century and provide the strongest available evidence that P. h. simalurus persists within the Simeulue Archipelago.